The South China Sea, ancient mercantile marine trade route, the 21st-century conflicts between the two great powers - Tamrongterakul, Sirirat; เพ็ชรประเสริฐ ณรงค์ (วารสารสังคมศาสตร์และมนุษยศาสตร์ มหาวิทยาลัยเกษตรศาสตร์, 2022)
The South China Sea (SCS) was a part of the ancient maritime trade route from the 2nd century BC until the 19th century. It was flourish during England’s mercantilism period (16th-18th century) and has become a part of the 21st century Belts and Roads Initiatives Maritime Route. Currently, the SCS is the conflict in the Asian region. It is also the area that maintains a regional balance of power between China and the United States and the US’s alliances. This research is based on secondary data retrieving information from the summarizing and collating existing documents mostly from online sources with reliable references. This research aims to analyze the involvement of the US in the SCS’s disputes and all disputed nations’ reactions. In conclusion, the authors concluded that with a bully strategy, China will lose support from ASEAN and would delay its BRI success. And it would not be a good choice for the US to initiate any war in this region amid its current hegemonic instability.